Ruch liniowego układu dynamicznego po losowo nierównej belce na sprężystym podłożu - CHUDZIKIEWICZ, Andrzej (Engineering Transactions, 1971)
Motion of a linear system on the uneven beam on an elastic foundationsA dynamic system with elastic and viscous bonds is moving on the undulated surface of an indefinitely long beam on elastic foundations. The undulations are defined as the stationary stochastic input process z(ξ).The manner of obtainment of the stochastic characteristics of the output processes ui(t), y(t, x) by correlation analysis is shown, with more detailed analysis for the one-degree-of-freedom system.The solution can be evaluated by numerical integrations.